The Influence of Price and Service Quality on Customer Satisfaction at PT Sarana Estate - Aris Ariyanto (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
This study aims to determine the effect of price and service quality on customer satisfaction at PT. Estate Facilities. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study have a significant effect on customer satisfaction by 41.5%, the hypothesis test obtained tcount> ttable or (8.130> 1.986). Service quality has a significant effect on customer satisfaction by 43.1%, the hypothesis test is obtained tcount> ttable or (8,401> 1,986). Price and quality of service simultaneously have a significant effect on customer satisfaction by 52.8%, the hypothesis test is obtained Fcount> Ftable or (51,366> 2,700).